The effect of caffeine consumption habits of contact tracing teams on anxiety, insomnia, and cardiac symptoms during the COVID-19 pandemic period: - Selçuk, Hatice; Karakaş, Neşe (Progress in Nutrition, 2022)
Purpose: The aim of this study was to examine the caffeine consumption habits and insomnia and anxiety levels of the personnel working in the contact tracing teams in the COVID-19 pandemic and to reveal their relationship with each other and with cardiac symptoms.Design and Methods: The population of this cross-sectional study consisted of the personnel working in contact tracing teams affiliated with a provincial health directorate.  Data were collected with online questionnaire forms. There are questions intended for the descriptive characteristics, caffeine consumption habits, and cardiac symptoms of the participants, Beck Anxiety Inventory and Insomnia Severity Index in the questionnaire form consisting of three parts.Results: Mild anxiety was detected in 12.0% of the participants, and medium and severe anxiety in 23.6%. The insomnia rate in the participants was found to be 35.6%. A positive correlation was detected between the anxiety scores of the participants and insomnia scores and the number of cardiac symptoms; as their daily caffeine consumption increased, the anxiety, insomnia, and the number of cardiac symptoms increased as well. Practice Implications: Psychological support for healthcare professionals like the contact tracing team working with infected patients in the pandemic period must be ready to be given when necessary.